2017
DOI: 10.1371/journal.pone.0183034
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macroinfaunal community structure, resource utilisation and trophic relationships in two Canadian Arctic Archipelago polynyas

Abstract: Climate change driven alterations to patterns of Arctic marine primary production, with increasing phytoplankton-and decreasing ice algal production, have the potential to change the resource utilisation and trophic structure of the benthic communities relying on the algae for food. To predict the benthic responses to dietary changes, we studied the macroinfaunal community compositions, and used the faunal δ ) recorded in NOW were higher than previously found in the Arctic at depths >500m, and significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 131 publications
(207 reference statements)
0
10
0
Order By: Relevance
“…Sea-ice extent and thickness are declining in the Arctic Ocean (Pizzolato et al 2014, Harada 2016 and in the Canadian Arctic (Environment andClimate Change Canada 2016, Stroeve &Notz 2018), causing alterations in timing, magnitude and spatial distribution of primary production in the sea ice and the water column (Ardyna et al 2014, Assmy et al 2017, Blais et al 2017. This yields profound implications for the dependent ice-associated, pelagic and benthic food webs in the Canadian Arctic (Hobson et al 2002, Roy et al 2015, Mäkelä et al 2017) and other Arctic near-shelf locations (McMahon et al 2006, Søreide et al 2013 as well oceanic regions (Kohlbach et al 2016(Kohlbach et al , 2017. Chan ges at the base of the food web will affect the energy flow from lower to higher trophic levels with un certain consequences for top predators (Hays et al 2005, Wassmann 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Sea-ice extent and thickness are declining in the Arctic Ocean (Pizzolato et al 2014, Harada 2016 and in the Canadian Arctic (Environment andClimate Change Canada 2016, Stroeve &Notz 2018), causing alterations in timing, magnitude and spatial distribution of primary production in the sea ice and the water column (Ardyna et al 2014, Assmy et al 2017, Blais et al 2017. This yields profound implications for the dependent ice-associated, pelagic and benthic food webs in the Canadian Arctic (Hobson et al 2002, Roy et al 2015, Mäkelä et al 2017) and other Arctic near-shelf locations (McMahon et al 2006, Søreide et al 2013 as well oceanic regions (Kohlbach et al 2016(Kohlbach et al , 2017. Chan ges at the base of the food web will affect the energy flow from lower to higher trophic levels with un certain consequences for top predators (Hays et al 2005, Wassmann 2015.…”
Section: Introductionmentioning
confidence: 99%
“…As our measurements were taken at a time when SCOC rates in NOW and LS are usually at their annual peak, it is possible that the effect of the algal addition was masked by the already high background SCOC. The sediment C:N ratio (6.5 at both sites) and organic matter (10−11%) and chl a (13−21 mg dry weight m −2 ) contents recorded at NOW and LS during sampling indeed suggest recent deposition of labile orga nic matter (Mäkelä et al 2017b). A similar dampening effect has also been suggested by Sun et al (2007), who observed algal addition to have no marked effect on SCOC in Smeerenburg Fjord, Svalbard, where the sediments had a high initial orga nic matter loading and surface sediment chl a content of < 2.5 µg g −1 dry sediment.…”
Section: Benthic C Respirationmentioning
confidence: 79%
“…Bacterial uptake of C IA and C PP was also significant, with 33−44% of the total C processing directed towards bacterial assimilation and growth, which was also illustrated by the high bacterial growth efficiency and rapid increase in bacterial biomass after algal additions. Interestingly, despite the high macroinfaunal biomass and density at both LS and NOW (Mäkelä et al 2017b), the role of these fauna, mainly polychaetes and crustaceans in NOW and polychaetes and bivalves in LS, in the processing of C IA and C PP was negligible. However, the overall biological processing in neither LS nor NOW seems to correspond with the categories of labelled C processing patterns identified by Woulds et al (2009Woulds et al ( , 2016.…”
Section: Total Processing Of C Pp and C Iamentioning
confidence: 95%
See 2 more Smart Citations